2022
DOI: 10.3390/v14050890
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Immunogenicity in Mice Orally Immunized with Recombinant Lactobacillus casei Expressing Porcine Epidemic Diarrhea Virus S1 Protein

Abstract: Porcine epidemic diarrhea (PED), characterized by diarrhea, vomiting, and dehydration, is an acute enteric infectious disease of pigs. The disease is caused by porcine epidemic diarrhea virus (PEDV), which infects the intestinal mucosal surface. Therefore, mucosal immunization through the oral route is an effective method of immunization. Lactic acid bacteria, which are acid resistant and bile-salt resistant and improve mucosal immunity, are ideal carriers for oral vaccines. The S1 glycoprotein of PEDV mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Another in vivo study demonstrated induction of innate and adaptive immune responses by L. acidophilus NCFB 1748 and L. paracasei DC412 on BALB/c inbred mice and Fisher-344 inbred rats through polymorphonuclear (PMN) cell recruitment, TNF-α secretion and phagocytosis ( Azad et al, 2018 ). Lactobacilli encode for certain motifs within their genome, such as unmethylated CpG motifs which are recognized by TLRs that are expressed particularly in B cells and macrophages ( Xiao et al, 2022 ). The role of Lactobacillus spp.…”
Section: Genus Lactobacillus and Human Healthmentioning
confidence: 99%
“…Another in vivo study demonstrated induction of innate and adaptive immune responses by L. acidophilus NCFB 1748 and L. paracasei DC412 on BALB/c inbred mice and Fisher-344 inbred rats through polymorphonuclear (PMN) cell recruitment, TNF-α secretion and phagocytosis ( Azad et al, 2018 ). Lactobacilli encode for certain motifs within their genome, such as unmethylated CpG motifs which are recognized by TLRs that are expressed particularly in B cells and macrophages ( Xiao et al, 2022 ). The role of Lactobacillus spp.…”
Section: Genus Lactobacillus and Human Healthmentioning
confidence: 99%
“…Xiao et al utilized the strain L. casei deficient in the upp gene to express the PEDV S1 protein, orally immunized mice, and measured cytokine levels. The data revealed the successful induction of Th1, Th2, and Th17 cell immune responses (Xiao et al 2022 ). Zhang et al developed the alanine racemase-deficient L. casei complementary system to express the VP4 gene of porcine rotavirus.…”
Section: Discussionmentioning
confidence: 97%
“…The plasmid pLCNICK (Song et al 2017 ), including the thermosensitive replicon, NCas 9 protein, and sgRNA sequence, was generously provided by Yang Sheng (a researcher at the Institute of Plant Physiology and Ecology, Shanghai Institutes for Biological Sciences, Chinese Academy of Sciences). Plasmids pMD-19Ts-P776 (Yin et al 2016 ), pMD-19Ts-RBS, and pMD-19Ts-S1 (Xiao et al 2022 ) were preserved in our laboratory. The PEDV LJB2019 strain was isolated from clinical samples and stored at − 140 °C to maintain its virulence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, researchers have expressed partial S protein, including the collagenase equivalent domain (COE), receptor binding domain (RBD) and S1, or the full-length S protein of individual SECs using E. coli , Lactobacillus , Bacillus subtilis , yeast, 293T cells, virus expression system (e.g., vesicular stomatitis virus, swinepox virus, pseudorabies virus, baculovirus, and human adenovirus), or transgenic plant expression systems ( Table 3 ). Among them, the immunogenicity of 14 vaccine candidates was evaluated in mice [ 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ]. All these vaccine candidates induced high levels of the virus-specific IgG and VN antibodies in serum and cytokines in splenocytes.…”
Section: Sec Vaccine Development In Chinamentioning
confidence: 99%